Mergers and Acquisitions for Business Sustainability in Emerging Markets During a Vague Era: A Literature Analysis (2022)
Mergers and acquisitions are the most popular modes of external corporate growth. Business sustainability, which seeks present returns without compromising the ability to earn returns in the future, has come under serious challenges in an environment of uncertainty. While academic literature suggests that in periods of fundamental uncertainty, there is a decline of mergers and acquisitions, this paper analyses an emerging body of research that suggests that merger and acquisition deals in a vague era actually deliver more value compared to those made in normal economic conditions, which most empirical studies do not deliver much value for the acquirer. This paper therefore suggests that firms in emerging markets can use mergers and acquisitions during a downturn to deliver superior value to shareholders. It also argues that mergers and acquisitions are a corporate governance issue, because it is at the board level that the overall strategy of the firm is implemented, including the various growth options of the firm. However, further research on merger and acquisitions during a vague era need to be conducted in various regions of emerging markets.